Acute kidney injury and in-hospital mortality among patients with COVID-19 in Ghana – a single centre study - Tannor, Elliot Koranteng; Ofori, Emmanuel; Hutton-Mensah, Kojo Awotwi; Akutek, Martin; Afriyie, Felicia Akua; Nyarko, Obed Ofori; Hardy, Yasmine; Kontoh, Samuel Amoabeng; Opare-Addo, Priscilla Abrafi; Amenuke, Divine (African Journal of Nephrology, 2023)
Introduction: Acute kidney injury (AKI) occurs in patients with coronavirus disease 2019 (COVID-19) and is associated with high mortality, but this has not yet been described in Ghana. We therefore record here the proportion of COVID-19 patients with AKI, and determined the corresponding mortality, in a tertiary-level hospital in Ghana. Methods: We conducted a retrospective study of all patients admitted to the Komfo Anokye Teaching Hospital, with a diagnosis of COVID-19 proven by reverse transcriptase polymerase chain reaction (RT-PCR), from March 2020 to February 2021. Demographics, clinical findings and laboratory investigations were recorded and summary statistics used to describe the data. Predictors of mortality were established by multiple logistic regression. Results: The study involved 250 patients, of whom 129 (52%) were males, with a mean age of 56.3 ± 17.4 years. AKI occurred in 123 (49%). The most common causes of AKI were pre-renal AKI and ischaemic ATN – 65 (73%) and 37 (30%) cases, respectively. Haemodialysis was required in 6 (5%) cases. The in-hospital mortality of all the COVID-19 patients was 71 (31%). The predictors of in-patient mortality in multivariate analysis were hyperglycaemia (OR = 18.48 [95%CI (2.0 –165.2], P = 0.009), severe COVID-19 (OR = 31.3 [95% CI 1.53–635.5], P = 0.025), elevated white blood cell count (OR = 1.32 [95% CI 1.09–1.59], P = 0.004), lymphopenia (OR = 0.16. [95% CI 0.03–3.26], P = 0.027) and not AKI (OR = 0.79 [95% CI 0.45–1.34], P = 0.380). Stage 3 (severe) AKI, however, occurred in 39 (32%) cases and was significantly associated with mortality [OR = 2.41 (95% CI 1.05–5.49, P = 0.036)] as compared to those with mild–moderate AKI in a sub-analysis. Conclusions: AKI is common in hospitalized patients with COVID-19. Stage 3 AKI was associated with increased in-hospital mortality. Predictors of mortality were severe COVID-19 disease, lymphopenia and hyperglycaemia.